2018
DOI: 10.1086/699327
|View full text |Cite
|
Sign up to set email alerts
|

In situ fluorometry reveals a persistent, perennial hypolimnetic cyanobacterial bloom in a seasonally anoxic reservoir

Abstract: Cyanobacterial blooms are increasing in waterbodies worldwide because of anthropogenic forcing. Most blooms occur at the water's surface, but some cyanobacterial taxa, such as Planktothrix, are able to modify their buoyancy to access more favorable growing conditions in deeper waters. Here, we used in situ fluorometry to examine the vertical distribution and biomass of Planktothrix in a seasonally anoxic reservoir for 3 consecutive summers. We also collected depth profiles of photosynthetically active radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Consistent with our observations, others have observed metalimnetic DCLs most commonly occuring at depths of less than 15 m, particularly those dominated by bloom-forming cyanobacteria [ 4 , 5 , 7 , 31 , 34 , 38 , 44 , 45 , 46 ]. Although significant DCLs dominated by potentially toxic cyanobacteria such as Planktothrix have been reported at depths below 15 m (e.g., [ 47 ]), this appears relatively rare [ 7 , 46 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our observations, others have observed metalimnetic DCLs most commonly occuring at depths of less than 15 m, particularly those dominated by bloom-forming cyanobacteria [ 4 , 5 , 7 , 31 , 34 , 38 , 44 , 45 , 46 ]. Although significant DCLs dominated by potentially toxic cyanobacteria such as Planktothrix have been reported at depths below 15 m (e.g., [ 47 ]), this appears relatively rare [ 7 , 46 ].…”
Section: Resultssupporting
confidence: 92%
“…There is a considerable body of evidence to indicate that the development of opposing and intersecting vertical gradients of light and nutrients is strongly correlated with DCL formation in stratified, meso-oligotrophic systems [ 4 , 5 , 7 , 15 , 34 , 44 ]. Our survey showed that stratified Georgian Bay embayments lacking these opposing and intersecting vertical gradients also lacked discernible DCLs.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of previous studies of DCMs examined only the vertical distributions of total phytoplankton biomass or of a single taxon (Christensen et al 1995;Jeppesen et al 2003;Kononen et al 2003;Hamilton et al 2010;Hamre et al 2018;Leach et al 2018), which could in part explain why there are so many different hypotheses and explanations for different DCM characteristics. Examination of total biomass obscures differences in the relative importance of top-down and bottom-up controls for different phytoplankton taxa.…”
mentioning
confidence: 99%
“…The depth and magnitude of DCMs may be driven by multiple physical, chemical, or biological factors, as DCMs can exist due to phytoplankton migration, growth, settling, or entrainment (Moll et al 1984; Arvola et al 1992; Durham and Stocker 2011). DCM depth may be determined by light attenuation, in which water columns with greater light penetration display deeper, broader DCMs (Varela et al 1994; Hamilton et al 2010; Leach et al 2018), or by a combination of light attenuation and nutrients, in which phytoplankton select a depth to optimize both down‐welling light and greater nutrient availability in hypolimnetic waters (Klausmeier and Litchman 2001; Karpowicz and Ejsmont‐Karabin 2017; Hamre et al 2018). Motile or buoyant phytoplankton will migrate to take advantage of these gradients of light, nutrients, or temperature and develop DCMs in layers with optimal resources (Moll et al 1984; Camacho et al 2001; Sengupta et al 2017).…”
mentioning
confidence: 99%
“…In addition to efficient absorption in the visible light spectrum, cyanobacteria have a protein structure that allows them to use light in the far-red spectrum, giving them a further advantage for growth under severe light extinction (Kirk 1994). The capacity to effectively adapt to low irradiance at depth (often far <1% of incident light; Hamre et al, 2018) demonstrates that cyanobacteria are well adapted to not only the low light conditions of eutrophic lakes, but also the deep chlorophyll maxima that are often present in meso-and oligotrophic lakes (e.g. Planktothrix rubescens, Cyanobium sp., and Aphanizomenon flos-aquae; Scofield et al, 2017.…”
Section: Lightmentioning
confidence: 99%